Mean recurrence interval a criterion for the determination of the directional design wind loads on structures - Aldecoa, Salvador Regachuelo (1993)
Wind load standards and codes govern design of buildings and structures to resist wind induced loads. A major portion of wind engineering research effort ultimately translated into development of wind loading standards. With the advent of wind tunnel tests and computer simulatons, wind direction is a very important aspect in structural design. This thesis focused on the sixteen univariate probability distributions of the largest yearly wind speeds recorded for the principal compass directions; obtained the design wind speed for each compass directions using the mean recurrence interval as the design criterion for the determination of wind loading. This thesis compared the results derived by directional wind speed based on sixteen univariate probability distributions, extreme yearly wind speed without considering its directions and the deterministic approach adopted by the National Structural Code of the Philippines (NSCP) committee on wind loading. Model parameters of extreme value distributions (Type I, Type Ia, Type II, and Type III) were estimated using the daily directional wind speed recorded at PAGASA weather station in Legaspi City. The Kolmogorov-Smirnov, Goodness-of-Fit Tests were used to test the validity of the probabilistic model
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Wind-pressure.; Structural dynamics; Winds -- Speed -- Philippines -- Legaspi City